Inbreds, Inbreeding Depression and Tuber Qualities of S1 and S2 Progenies in Taro (Colocasia esculenta L. Schott) - Geethakrishnan Nair, Parameswaran Pillai; Santha Pillai, V (JOURNAL OF ROOT CROPS, 2015)
Abstract Taro is a perennial herbaceous tuber bearing plant belongs to the family of Araceae. The tubers are good source of starch and dietary fiber content (4.3g per 100g fresh tuber). Preliminary work on selfing reported that variation was less in the selfed progeny than in the open pollination and it was possible to concentrate resistance genes towards leaf blight. Hence inbreeding was done in taro to identify the extent of selfing possible and to develop good genetic stocks for different characters. 350 accessions of germplasm and 10 breeding lines from CTCRI, 42 collections from North Eastern Hill region of India, six local collections were screened for flowering. The flowering accessions range from 1.72 . 9.83 % only in various seasons. 25 first generation selfed progenies (S1) and five second generation selfed progenies (S2) were obtained and 16 S1 and five S2 progenies were raised and analyzed for inbreeding depression, cooking quality, starch and sugar content. The phenotypic characters in the progenies except for cormel shape did not show remarkable variations. The S1 progenies were evaluated for yield and 49 inbreds were selected with cormel yield >300 g/plant. Among 97 selected S1 lines with yield above 100g/plant and good cormel shape, 35.1% were with non- acrid and soft tubers. In S1 progenies, starch content on fresh weight basis range from 11.8 . 33.1% and sugar 1.1 - 3.2%. Inbreeding depression was evident in the weight of corm (1.62%) and weight of cormel (4.72%). The number of corm showed significant negative inbreeding depression(- 14.44%) and the same in cormel number was (-)4.59%. There was varietal difference with respect to inbreeding depression which can be made use of for production of superior inbreads. Key words : Inbreeding, Inbreds, Inbreeding depression, selfed progenies, corm, cormel, taro